Pengaruh Profitabilitas Terhadap Internet Financial Reporting (IFR) - Agustina, Duwi; Yanto, Yanto (ARBITRASE: Journal of Economics and Accounting, 2022)
Financial reporting via the internet is the disclosure of financial information using the company's own website. With the development of information technology, all work and human activities can be completed effectively and more efficiently. Financial reporting via the internet is expected to improve a company's communication with external and internal parties of the company, as well as other parties related to the company. The purpose of this research is to determine the effect of the independent variable namely Profitability on the dependent variable, namely Internet Financial Reporting on the company manufacturers listed on the IDX for the 2019-2020 period. The type of research used is explanatory research with data collection techniques using secondary data. The object of this research is a manufacturing company listed on the IDX for the 2019-2020 period. The number of samples in this study were 72 companies using SPSS. The data analysis technique used in the study uses simple linear regression analysis. The results of this study indicate that the profitability variable has no effect on Internet Financial Reporting.